ANALISIS KINERJA KEUANGAN BERBASIS ECONOMIC VALUE ADDED (EVA) PADA PT. BANK SULUTGO - Sondakh, Marcelino; Mangindaan, J. V.; Keles, Dantje (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
The purpose of this study is to find out how much Economic Value Addedgenerated by PT. Bank SULUTGO in 2014-2016. It is known that PT. Bank SULUTGOis a regional bank of North Sulawesi and Gorontalo which owns shares from variousregions and several companies. It is known that the capital annually PT. BankSULUTGO in 2014-2016 always increases. But with the increase in capital whether ithas made the company able to improve the performance of the company or increase therevenue of the company so as to be able to distribute the fair share of the results to theshareholders of the company. The purpose of this study is "Financial PerformanceAnalysis Based on Economic Value Added at PT. Bank SULUTGO". Financialperformance is needed by the company to evaluate the performance or as a foundationof the company to improve the company's performance. Financial performanceaccording to Ikatan Akuntansi Indonesia (2007) is the determination of the company'sability to manage and control its own resources. While EVA is an effectivecommunication tool for value creation that can be reached by line managers thatultimately drive company performance and to connect with capital markets (Young andO'Bryne, 2001). The research method used is quantitative descriptive method by usinganalysis tools in the form of Economic Value added to calculate NOPAT, InvestedCapital, WACC, Capital Charges and EVA. Based on the results of research EVAanalysis at PT. Bank SULUTGO 2014-2016 year turned out to fluctuate because EVAcompanies every year down and up. Nevertheless PT. Bank SULUTGO turned out tohave created a positive value in the company in 2014-2016. In 2014 the company is ableto create EVA of Rp. 97,596 (in millions of rupiah), but in 2015 the company's EVAdecreased by 26.08% to Rp. 72,140 (in millions of rupiah) and in 2016 again increasedby 34.01% to Rp. 96,680 (in millions of rupiah). Thus the management has been able tocreate a positive value on the company well and shareholders can entrust theirinvestment to the company.Keywords: Economic Value Added (EVA), Financial Performance